2012
DOI: 10.1177/0009922811435504
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Dog Bite Victims

Abstract: The authors assessed the ongoing needs of 34 pediatric dog bite victims and their families 1 month after receiving care in a pediatric emergency department. More than 70% of the parents noted at least 1 new concerning behavior in their children, and more than 85% of the parents also endorsed concerns about their own reactions. Half of the parents believed that children, in general, might benefit from interventions to help with postbite fears and nearly three quarters felt that families would benefit from educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Studies have demonstrated a spectrum of psychological disturbance in children following a dog bite from avoidance behaviours to formal diagnosis of post-traumatic stress disorder (PTSD). 16 Boat et al 15 found that in more than 70% of dog bite cases, parents reported at least one new concerning behaviour. Nearly a third of children demonstrated a new fear or avoidance of dogs and one-fifth experienced nightmares following the incident.…”
Section: Psychological Impactsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have demonstrated a spectrum of psychological disturbance in children following a dog bite from avoidance behaviours to formal diagnosis of post-traumatic stress disorder (PTSD). 16 Boat et al 15 found that in more than 70% of dog bite cases, parents reported at least one new concerning behaviour. Nearly a third of children demonstrated a new fear or avoidance of dogs and one-fifth experienced nightmares following the incident.…”
Section: Psychological Impactsmentioning
confidence: 99%
“…It is also important to note that there is a psychological impact on the carers of paediatric victims. Boat et al 15 found that 85% of parents whose child sustained a dog bite injury reported changes in their own feelings following the incident. Two-thirds reported feelings of guilt and just under half reported feeling angry or fearful for their child's safety.…”
Section: Psychological Impactsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been reported that 43% of patients on a maxillofacial ward for treatment after a dog bite were children under the age of 10 ( 40 ). Such injuries can lead to life-threatening medical conditions or psychological sequelae like Post-Traumatic Stress Disorder ( 51 , 52 ). Whilst physical injuries are apparent, the psychological impact is less obvious, and left untreated can have long term consequences, not only for the victim but also their family ( 52 ).…”
Section: Introductionmentioning
confidence: 99%
“…Such injuries can lead to life-threatening medical conditions or psychological sequelae like Post-Traumatic Stress Disorder ( 51 , 52 ). Whilst physical injuries are apparent, the psychological impact is less obvious, and left untreated can have long term consequences, not only for the victim but also their family ( 52 ). Seventy percent of all fatal dog bites involve children ( 53 , 54 ).…”
Section: Introductionmentioning
confidence: 99%